Tinjauan Pendidikan Kristiani tentang Pengendalian Diri dalam Menakar Fenomena Self Reward bagi Calon Katekis - Angelina Febrianty Mukin; Monica Innanda Chiaralazzo; Intansakti Pius X (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The phenomenon of self-reward is increasingly popular among young people, including prospective catechists, as a response to personal achievements. However, this practice has the potential to lead to a consumptive lifestyle that neglects spiritual values. Christian education plays an important role in shaping the self-control of prospective catechists to manage self-reward wisely, thus preventing disruption to their spiritual balance. The purpose of this study is to explore how Christian education can develop self-control in dealing with the self-reward phenomenon. This study employs a qualitative approach with literature review methods and in-depth interviews with prospective catechists actively involved in church education. The results show that prospective catechists who receive Christian education focused on character and spiritual development are better able to distinguish between genuine spiritual needs and temporary worldly desires. Christian education plays a key role in teaching self-control that strikes a balance between personal satisfaction and spiritual goals. In conclusion, self-control taught in Christian education can help prospective catechists face the temptation of a consumptive lifestyle and become life examples that better align with Christ’s teachings.